2009
DOI: 10.1111/j.1349-7006.2009.01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of podoplanin, CD44, and p63 in squamous cell carcinoma of the lung

Abstract: Recent molecular biological studies have identified podoplanin as a candidate cancer stem cell (CSC) marker in squamous cell carcinoma (SqCC). The purpose of this study was to examine the expression pattern of podoplanin, and the other stem cell markers CD44 and p63, and their relationship to clinico-pathological features including survival in pulmonary SqCC. We examined histologically the expression of podoplanin, CD44, and p63 in 162 consecutive SqCC by immunostaining. Podoplanin expression was observed in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
78
4
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 25 publications
10
78
4
1
Order By: Relevance
“…Shimada et al reported that podoplanin expression reflected the immature status in lung squamous cell carcinoma cells. They also found that immunostaining of podoplanin, CD44 and p63 and analysis of the hierarchical distribution patterns of the markers in the tumor nests revealed cells with a capacity for further maturation (24). Long et al demonstrated that SOX2 was implicated in the maintenance of pluripotency and esophageal epithelial development, and that it was preferentially expressed in ESCC (13).…”
Section: Discussionmentioning
confidence: 99%
“…Shimada et al reported that podoplanin expression reflected the immature status in lung squamous cell carcinoma cells. They also found that immunostaining of podoplanin, CD44 and p63 and analysis of the hierarchical distribution patterns of the markers in the tumor nests revealed cells with a capacity for further maturation (24). Long et al demonstrated that SOX2 was implicated in the maintenance of pluripotency and esophageal epithelial development, and that it was preferentially expressed in ESCC (13).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report to clarify the relationship between podoplanin membrane expression and clinicopathological factors. Shimada et al reported that positive podoplanin expression was significantly correlated with better prognosis of lung SqCC (24). Using immunohistolung SqCC (HR, 2.830; 95% CI, 1.456-5.500, P = 0.002) ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Strong podoplanin expression was significantly correlated with peripheral type (P < 0.001), with a correlation coefficient of 0.678. Recently, podoplanin has been considered as one of the candidate markers of cancer stem cells, associated with cancer cell invasion or migration, as well as the prognosis of several cancers (12,24,28,29,33). Several studies have clarified that podoplanin expression promotes epithelial-to-mesenchymal transition in morphogenetic processes.…”
Section: Relationships Between Podoplanin Intensity and Localizationmentioning
confidence: 99%
“…Lymphatic vessel density examined using an antibody to podoplanin has been reported to be a prognostic factor in lung cancer (4)(5)(6). Podoplanin is also expressed in tumor cells in lung cancer (7)(8)(9)(10)(11), and is considered to regulate tumor progression and metastasis through various mechanisms, including epithelial-mesenchymal transition and platelet aggregation (12)(13)(14). Several previous studies reported that podoplanin expression in tumor cells in lung SCC was correlated with a lower incidence of lymph node metastasis and good prognosis (7)(8)(9)(10), whereas another study reported that it was associated with poor prognosis (11).…”
mentioning
confidence: 99%
“…Podoplanin is also expressed in tumor cells in lung cancer (7)(8)(9)(10)(11), and is considered to regulate tumor progression and metastasis through various mechanisms, including epithelial-mesenchymal transition and platelet aggregation (12)(13)(14). Several previous studies reported that podoplanin expression in tumor cells in lung SCC was correlated with a lower incidence of lymph node metastasis and good prognosis (7)(8)(9)(10), whereas another study reported that it was associated with poor prognosis (11). Highpodoplanin expression is also observed in stromal fibroblasts, or so-called cancer-associated fibroblasts (CAFs), in lung adenocarcinoma and SCC, which has been shown to be unfavorable prognostic factor (15,16).…”
mentioning
confidence: 99%